Identification of modal strains using sub-microstrain FBG data and a novel wavelength-shift detection algorithm. (1st March 2017) - Anastasopoulos, Dimitrios; Moretti, Patrizia; Geernaert, Thomas; De Pauw, Ben; Nawrot, Urszula; De Roeck, Guido; Berghmans, Francis; Reynders, Edwin
Abstract: The presence of damage in a civil structure alters its stiffness and consequently its modal characteristics. The identification of these changes can provide engineers with useful information about the condition of a structure and constitutes the basic principle of the vibration-based structural health monitoring. While eigenfrequencies and mode shapes are the most commonly monitored modal characteristics, their sensitivity to structural damage may be low relative to their sensitivity to environmental influences. Modal strains or curvatures could offer an attractive alternative but current measurement techniques encounter difficulties in capturing the very small strain (sub-microstrain) levels occurring during ambient, or operational excitation, with sufficient accuracy. This paper investigates the ability to obtain sub-microstrain accuracy with standard fiber-optic Bragg gratings using a novel optical signal processing algorithm that identifies the wavelength shift with high accuracy and precision. The novel technique is validated in an extensive experimental modal analysis test on a steel I-beam which is instrumented with FBG sensors at its top and bottom flange. The raw wavelength FBG data are processed into strain values using both a novel correlation-based processing technique and a conventional peak tracking technique. Subsequently, the strain time series are used for identifying the beam's modal characteristics. Finally, the accuracy of both algorithms in identification of modal characteristics is extensively investigated. Abstract : Highlights: Modal strains are attractive for SHM because of the high sensitivity to local damage. Operational strain levels are often in the sub-microstrain range. Sub-microstrain accuracy is obtained with standard FBGs and a novel optical signal processing algorithm. Subsequent system identification leads to accurate modal strains. Both bending and torsion warping strain mode shapes of an I-shaped steel beam are accurately identified.